Learn Idioms Using Augmented Reality - Nur Amalia Atikah Edyanto; Siti Zalifah Ramli; Nur Ain Najihah Ibharim; Siti Aishah Zahari; Muhammad Asyraf Abdullah Zawawi (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
English language is international language that are worldwide use and also one of the important language in communication and a main-medium of instruction in education in Malaysia. In order to become good in English we must learn since we were kids like since preschool and primary school and that show how important to learn English language. Then it need to help the students especially the pre-school and the primary school students to learn English in more effective and attractive ways so that they will not feel boring or lost interest in learning English language. Aim of this research is to find an interactive tool that can be used in learning an English idioms. This research use RAD Model to develop AR application and quantitative methods through questionnaires were implemented to evaluate the research that were developed. The research was evaluated by 10 teachers who teach English Language and evaluated based on usefulness, satisfaction and ease of use questionnaires.